Thin film composite membranes functionalized with montmorillonite and hydrotalcite nanosheets for CO2/N2separation - Zhang, Y.; Wang, H.; Zhang, Y.; Ding, X.; Liu, Jian (Pergamon Press, 2017)
© 2017 Elsevier B.V. Montmorillonite (MMT) and Mg-Al hydrotalcite (HT) nanosheets were prepared via vigorous agitation and ultrasonic, respectively. In order to increase the permeability of CO2, poly (PEA-MMT-TMC)/PS and poly (PEA-HT-TMC)/PS composite membranes were prepared via interfacial polymerization by adding the dimensional (2D) inorganic nanosheets (MMT and HT) into the aqueous phase of PEA. And in consequence, the poly (PEA-MMT-TMC)/PS composite membrane showed CO2permeability of 15.87 barrer and the CO2/N2selectivity of 37 at 1.0 bar when the MMT concentration was 0.068 wt%. The poly (PEA-HT-TMC)/PS composite membrane also showed CO2permeability of 15.3 barrer and the CO2/N2selectivity of 40 at 1.0 bar when the HT concentration was 0.25 wt%. Compared with the controlled membrane (CO2permeability: 6.9 barrer, CO2/N2selectivity: 103), the CO2permeability increased after incorporating the inorganic nanosheets into the membranes and maintained the pretty CO2/N2selectivity. The addition of exfoliated MMT and HT could facilitate the gas permeation to improve the gas separation performance of the composite membranes. Also, the combination of inorganic nanosheets with organic membrane has a great potential application in the gas separation.